2014
DOI: 10.1177/0956797614547916
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration in Complete Unawareness: Evidence From Audiovisual Congruency Priming

Abstract: Multisensory integration is thought to require conscious perception. Although previous studies have shown that an invisible stimulus could be integrated with an audible one, none have demonstrated integration of two subliminal stimuli of different modalities. Here, pairs of identical or different audiovisual target letters (the sound /b/ with the written letter “b” or “m,” respectively) were preceded by pairs of masked identical or different audiovisual prime digits (the sound /6/ with the written digit “6” or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
73
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 37 publications
5
73
3
Order By: Relevance
“…The results from the Faivre et al [3] study do not allow us unequivocally to answer this question. They do, however, provide important clues suggesting that the process may be taking place at the semantic level.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…The results from the Faivre et al [3] study do not allow us unequivocally to answer this question. They do, however, provide important clues suggesting that the process may be taking place at the semantic level.…”
mentioning
confidence: 88%
“…Earlier work has indicated that audible sounds can impact invisible pictures suppressed from awareness during binocular rivalry [2], but can auditory and visual signals interact when both are presented outside of awareness? A recent study by Faivre et al [3] provides an answer to this question by unequivocally demonstrating the interaction of subthreshold auditory and visual cues. Left unanswered, however, is whether this interaction represents genuine multisensory integration or, instead, arises from interactions at amodal, semantic levels of analysis (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). Subliminal priming generalizes across visualauditory modalities (7,8), revealing that crossmodal computations that remain challenging for AI software (such as extraction of semantic vectors or speech-to-text) also involve unconscious mechanisms. Even the semantic meaning of sensory input can be processed without awareness by the human brain.…”
Section: C2: Self-monitoringmentioning
confidence: 99%
“…First, unconscious processing of numerosity in vision is well documented, as invisible prime stimuli conveying either symbolic or nonsymbolic numerosity signals are known to induce priming effects under various techniques such as masking (Dehaene, Naccache, Le Clec', Koechlin, & Mueller, 1998), continuous flash suppression (Bahrami et al, 2010), or crowding (Huckauf, Knops, Nuerk, & Willmes, 2008;see Dubois & Faivre, 2014 for a comparison of various techniques used to make stimuli invisible). Second, cross-modal unconscious effects pertaining to numerosity processing are now well established, notably between a subliminal (i.e., consciously unaccessible) visual prime digit and a supraliminal (i.e., consciously accessible) auditory target (Kouider & Dehaene, 2009), and even between two subliminal audiovisual stimuli conveying numerosity information (Faivre, Mudrik, Schwartz, & Koch, 2014). Yet, while low-level interactions between a supraliminal tactile stimulus and a subliminal visual one are documented (Lunghi, Binda, & Morrone, 2010), no study to our knowledge has investigated cross-modal influences from subliminal stimulus in the tactile domain.…”
Section: Introductionmentioning
confidence: 99%